Critical rainfall for debris-flow generation in Catia La Mar - Courtel, Francois; López, José Luis; Gascón, Tania (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
A graphical relation is proposed in order to evaluate the possibility of debris-flow generation in the area of Catia La Mar, in the State of Vargas. The graphic uses two rainfall indicators, one indicator representing the short-term rainfall (recent hours) and the other one the long-term rainfall (recent days), to define a critical line which separates a safe zone from a risky zone. To determine the critical line in the evaluation graphic, a historic investigation was necessary as to represent both debris-flow events occurred in the past (causing rainfalls) and extreme past rainfalls that did not cause debris flows (non-causing rainfalls). The chart is currently being used as a tool in an early warning system that has been installed to protect the town of Catia La Mar. The system is composed by rainfall stations and water level stations that transmit real time data to a control station. The data will be used to calibrate and adjust the threshold line with the purpose of improving, progressively, the debris-flow-alert prediction in the region.